Effect of Rapid Rollover on Pneumothorax Rate After Percutaneous CT-Guided Lung Biopsy - Xiao Wu; Lynn Leng; Andrew Tong Li; Hannah Ahn; Sayedomid Ebrahimzadeh; Brett M. Elicker; Brian Haas; Kimberly Gray Kallianos; Yoo Jin Lee; Jonathan Aaron Liu; Jamie Lee Twist Schroeder; Shravan Sridhar; et al. (Journal of Thoracic Imaging, 2026)
Purpose: To evaluate whether the rapid rollover technique reduces new or enlarging pneumothorax after anterior or lateral approach CT-guided lung biopsy. Materials and Methods: A prospective, single-institution, multisite, RCT was undertaken after institutional review board approval. Patients with target lesions most amenable to the anterior/lateral approach were considered. Patients with extrapulmonary nodules, intraprocedural chest tube, or conditions that preclude safe repositioning were excluded. The primary outcome was new/enlarging pneumothorax on postbiopsy radiographs. Intention-to-treat (ITT) and per-protocol (PP) analyses were performed. Secondary outcomes, including chest tube insertion rate and patient discomfort, were also analyzed. Results A total of 59 patients were recruited, with 28 randomized to the intervention arm and 31 to the control arm, without significant differences in patient demographics and risk factors. There were 8 cases or 13.6% of new/enlarging pneumothorax, 7 from the control arm and 1 from the intervention. One patient who developed pneumothorax in the intervention arm did not complete the maneuver. The difference in rates of new/enlarging pneumothorax was significant by both ITT and PP analyses ( P =0.03 and 0.009). Only 2 patients required chest tube insertion, 1 in the control group and 1 who crossed over to the control group. Multivariate analysis was performed in the ITT analysis, with intervention as an independent significant factor ( P =0.0463). There were no significant differences in terms of postbiopsy discomfort. Conclusions: This randomized controlled trial showed that, without an increase in patient discomfort, the rapid rollover technique reduced the risk of new or enlarging pneumothorax after CT-guided lung biopsy via an anterior/lateral approach. Level of Evidence: Level I—randomized controlled trial.